Nuevas perspectivas sobre violencia intrafamiliar : un enfoque psicoanalítico (2010)
ABSTRACT: It is well-know the social sciences studies the domestic violence phenomenon from the approach of risk factors, as well as the therapeutic process that often propose some assailant conception translated into asistentialistic process. Otherwise, the psychoanalysis offer a different perspective, base on the symbolization of aggressive tendencies that all human being carry, in the question for the assailant position that victims often take from this assaults and the consistent promotion of subjective responsibility of the characters that take part in the domestic violence situation.